Efficacy of fungicides against peanut smut in Argentina - Paredes, Juan Andrés (2020)
Peanut smut, caused by Thecaphora frezii, increased its incidence and prevalence in the main growing region of Argentina in the last decade becoming the main peanut disease. Despite this fact, growers continue producing peanut without any disease management strategy, which is leading to a local accumulation of T. frezii inoculum. The goal of the present study was to assess the efficacy of 12 fungicides in controlling T. frezii. For this purpose, in vitro assays, pot, and field experiments were performed during 2014/15 and 2015/16. In vitro assays classified the fungicides regarding their capacity to inhibit T. frezii mycelium growth as: thiophanate-methyl – not fungitoxic (EC50 > 100); mancozeb – moderately fungitoxic (EC50 = 6.28); difenoconazole, propiconazole, cyproconazole, tebuconazole, picoxystrobin, azoxystrobin, kresoxim-methyl, pyraclostrobin, penthiopyrad, and chlorothalonil – highly fungitoxic (EC50 < 0.1). Azoxystrobin showed the highest control levels in pot experiments: 58.9% (2014/15) and 92% (2015/16). The greatest control efficiency in field experiments was observed for cyproconazole in 2015 and azoxystrobin in 2016, reducing peanut smut by 47.7% and 39.5%, respectively. Based on our results, chemical control can be considered as a moderately efficient practice which may complement the cultivar genetic resistance and cultural practices in an integrated approach for managing peanut smut.